Mechanism of charge transfer and its impacts on Fermi-level pinning for gas molecules adsorbed on monolayer WS2 - Zhou, Changjie (2015)
Density functional theory calculations were performed to assess changes in the geometric and electronic structures of monolayer WS2 upon adsorption of various gas molecules (H2, O2, H2O, NH3, NO, NO2, and CO). The most stable configuration of the adsorbed molecules, the adsorption energy, and the degree of charge transfer between adsorbate and substrate were determined. All evaluated molecules were physisorbed on monolayer WS2 with a low degree of charge transfer and accept charge from the monolayer, except for NH3, which is a charge donor. Band structure calculations showed that the valence and conduction bands of monolayer WS2 are not significantly altered upon adsorption of H2, H2O, NH3, and CO, whereas the lowest unoccupied molecular orbitals of O2, NO, and NO2 are pinned around the Fermi-level when these molecules are adsorbed on monolayer WS2. The phenomenon of Fermi-level pinning was discussed in light of the traditional and orbital mixing charge transfer theories. The impacts of the charge transfer mechanism on Fermi-level pinning were confirmed for the gas molecules adsorbed on monolayer WS2. The proposed mechanism governing Fermi-level pinning is applicable to the systems of adsorbates on recently developed two-dimensional materials, such as graphene and transition metal dichalcogenides.